EMPLOYEE RETENTION MODEL THROUGH PERCEIVED ORGANIZATIONAL SUPPORT: ANALYSIS OF CAREER DEVELOPMENT PRACTICES, ORGANIZATIONAL JUSTICE AND TRUST IN ORGANIZATION AUDITOR EMPLOYEES AT BPKP OFFICE - Sumardi; Hapzi Ali; Agung Dharmawan Buchdadi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
An organization's goal to be achieved is to improve existing performance for the better. This study discusses how companies retain skilled and qualified employees and what if those skilled and qualified employees leave the company within the Financial and Development Supervisory Agency (BPKP), especially employees with positions as auditors. Several factors driving employee turnover in the BPKP environment obtained the results of the Pre-survey conducted using the accidental sampling method with nine questions addressed to 33 respondents, namely employees who are currently no longer working at BPKP. The assessment carried out by the author is to use a Likert's Scale with an interval of 1 to 5, namely 1 (strongly disagree), 2 (counter), 3 (disagree), 4 (agree), and 5 (strongly agree). Based on a review of various influences and several previous studies to the best of the author's knowledge, no similar research has been found, namely regarding the effect of Career Development Practices (CDP), Organizational Justice (OJ), and Trust in Organization (TIO) on Employee Retention (ER) either directly or indirectly. They were mediated by Perceived Organizational Support (POS) that occurred within the auditor environment of the Financial and Development Supervisory Agency. The results of this study confirm the practice that has been going on at the BPKP Office, namely by improving employee career development practices. These various organizational actions reflect fairness and trust that are continuously built by the leadership and the more excellent support provided by the Organization so that employee retention is also getting better. In the period 2015 to 2020, the percentage of employees who left the BPKP Office decreased from 0.92% to 0.21%